PUBLIC SERVICE TRANSFORMATION THROUGH APPLICATIONS “LAPOR” IN THE CONTEXT OF E-GOVERNMENT IN DIGITAL ERA - Firman; Trijayanto, Danang; Rahmawati, Restu (ASPIRATION Journal, 2022)
The integration of e-government, especially with the use of the Lapor application, has increased the efficiency and accessibility of government services, the public can report problems or submit requests for services more easily through the Lapor application rather than having to visit government offices directly. This research aims to monitor increased community participation, reducing the time required for authorities to respond, and assessing the level of user satisfaction with the usability and effectiveness of public services through portal applications in the context of e-government. This research also focuses on evaluating the effectiveness of LAPOR! in responding to community aspirations and complaints during health emergencies. The unit of analysis referred to in the research includes an evaluation of the extent to which LAPOR! succeeded in facilitating communication between the government and the community during the Covid-19 pandemic. This research also uses normative juridical methods with a focus on library research to evaluate the extent to which the application affects the efficiency and accessibility of public services. Information or data is obtained from various library sources, including books, scientific journals, articles and literature related to research objectives. The data collection process was carried out through literature study, then qualitative analysis was carried out and the results were presented descriptively. The results of this research, namely the application of the concept of E-Government, or electronic-based government, shows great opportunities by utilizing information technology to improve the quality of public services and increase their effectiveness. These benefits include increased performance in terms of effectiveness and efficiency of public services. The significance of the findings shows that active community participation in using the LAPOR application can have a positive impact. This not only improves data accessibility for citizens but also enables more efficient feedback to the government.